Digital audiometer based on the "8748" microcontroller. - Martínez Báez, Celia; Medina Ruiz, Maria; Ayala Perdomo, Roberto (Revista Mexicana de Ingenieria Biomedica, 1989)
An equipment for aerial audiometry of tonal type is presented, with two modes of operation: manual and automatic. It generates 8 frequencies at 21 amplitude levels. It also allows masking by white noise. It also includes intercommunication with the patient. The microcontroller organizes all the functions, which are selected by specially designed membrane keypad.